2023
DOI: 10.1038/s41597-023-02146-7
|View full text |Cite
|
Sign up to set email alerts
|

High throughput calculations for a dataset of bilayer materials

Abstract: Bilayer materials made of 2D monolayers are emerging as new systems creating diverse opportunities for basic research and applications in optoelectronics, thermoelectrics, and topological science among others. Herein, we present a computational bilayer materials dataset containing 760 structures with their structural, electronic, and transport properties. Different stacking patterns of each bilayer have been framed by analyzing their monolayer symmetries. Density functional theory calculations including van de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Unstable phonon spectra for AC, AC ′′ , AA b ′′ , AB b ′′ and AC b ′′ stackings with negative modes are shown in figures S1 and S3 (ESI). Next, the interlayer binding (B.E) and adhesion (A.E) energies of only dynamically stable stackings are calculated by employing the following equations [46,47],…”
Section: Resultsmentioning
confidence: 99%
“…Unstable phonon spectra for AC, AC ′′ , AA b ′′ , AB b ′′ and AC b ′′ stackings with negative modes are shown in figures S1 and S3 (ESI). Next, the interlayer binding (B.E) and adhesion (A.E) energies of only dynamically stable stackings are calculated by employing the following equations [46,47],…”
Section: Resultsmentioning
confidence: 99%
“…The variation in adhesion energy is typically considered by constructing a potential energy surface tracking the energy for different stacking configurations at equilibrium separation between the materials. In this study, the reported stacking patterns for the BMDS with their equilibrium interlayer separations and corresponding DFT adhesion energies are calculated and taken to initiate the ML study of the bilayers tribological properties. , The stacking patterns are obtained by using combinations of different relative slidings and/or 180° rotations of the various lattices (see Figures S1–S11 in the Supporting Information and in ref and ).…”
Section: Resultsmentioning
confidence: 99%
“…Bilayered materials classes are denoted as CL-1 for 1T-AX 2 ( P true 3 ̅ m 1), CL-2 for 2H-AX 2 ( P true 6 ̅ m 2), CL-3 for 1T-AX 1 X 2 ( P 3 m 1), CL-4 for 2H-AX 1 X 2 ( P 3 m 1), CL-5 for 1T-A 2 X 2 ( P true 3 ̅ m 1), CL-6 for 2H-A 2 X 2 ( P true 6 ̅ m 2), CL-7 for Sq-AX 2 ( P true 4 ̅ m 2), CL-8 for Sq-A 2 X 2 ( P 4/ nmm ), and CL-9 for Hex-AX or A 2 . Nomenclature of stacking configurations, chemical formulas, and monolayer space groups can be found in the Supporting Information. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations